Mycobacterium leprae Infection in Ticks and Tick-Derived Cells - Tongluan, Natthida; Shelton, Layne T.; Collins, J. Hunter; Ingraffia, Patrick; McCormick, Gregory; Pena, Maria; Sharma, Rahul; Lahiri, Ramanuj; Adams, Linda B.; Truman, Richard W.; Macaluso, Kevin R. (Frontiers in Microbiology, 2021)
Leprosy is a zoonosis in the southern United States involving humans and wild armadillos. The majority of patients presenting with zoonotic strains of Mycobacterium leprae note extensive outdoor activity but only rarely report any history of direct contact with wild armadillos. Whether M. leprae is transmitted to new vertebrate hosts through the environment independently or with the aid of other organisms, e.g., arthropod vectors, is a fundamental question in leprosy transmission. The objectives of this study were to assess the potential for ticks to transmit M. leprae and to test if viable M. leprae can be maintained in tick-derived cells. To evaluate tick transmission, nymphal Amblyomma maculatum ticks were injected with isolated M. leprae. Infection and transmission were assessed by qPCR. Ticks infected as nymphs harbored M. leprae through vertical transmission events (nymph to adult and adult to progeny); and, horizontal transmission of M. leprae to a vertebrate host was observed. M. leprae DNA was detected in multiple tick life cycle stages. Likewise, freshly isolated M. leprae (Thai-53 and Br4923) was used to infect a tick-derived cell line, and enumeration and bacterial viability were assessed at individual time points for up to 49 days. Evaluation of the viability of long-term cultured M. leprae was also assessed in a mouse model. Tick-derived cells were able to maintain viable M. leprae over the 49-day course of infection and M. leprae remained infectious within tick cells for at least 300 days. The results of this study suggest that ticks themselves might serve as a vector for the transmission of M. leprae and that tick cells are suitable for maintenance of viable M. leprae for an extended period of time.